2008
DOI: 10.1289/ehp.10686
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Polychlorinated Biphenyls and Dioxins on Pregnancy Outcomes in Women Affected by the Yusho Incident

Abstract: BackgroundMaternal exposure to polychlorinated biphenyls (PCBs) is associated with increased proportions of spontaneous abortion and stillbirth in animal studies. In Japan in 1968, accidental human exposure to rice oil contaminated with PCBs and other dioxin-related compounds, such as polychlorinated dibenzofurans (PCDFs), led to the development of what was later referred to as Yusho oil disease.ObjectiveThe aim of this study was to investigate the association of maternal PCB and dioxin exposure with adverse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 29 publications
3
42
2
Order By: Relevance
“…Exposure was associated with reduced litter size, reduced placental and fetal weight, increased amniotic fluid, and defective righting reflex in newborns. These observations support the epidemiological reports on PCB-induced low birth weight and premature deliveries, postnatal low IQ and behavioral alterations, and high life time risks in humans (7,26,27,32). Importantly, we found that AQP1 is a novel in utero target of PCBs, linking amniotic fluid volume regulation and angiogenesis with toxicant-mediated effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Exposure was associated with reduced litter size, reduced placental and fetal weight, increased amniotic fluid, and defective righting reflex in newborns. These observations support the epidemiological reports on PCB-induced low birth weight and premature deliveries, postnatal low IQ and behavioral alterations, and high life time risks in humans (7,26,27,32). Importantly, we found that AQP1 is a novel in utero target of PCBs, linking amniotic fluid volume regulation and angiogenesis with toxicant-mediated effects.…”
Section: Discussionsupporting
confidence: 92%
“…Convincing evidence exist for their toxicity, both in humans as well as in laboratory animals (7). From epidemiological studies in humans it has been observed that exposure to PCBs causes various reproductive anomalies that include irregular and shorter menstrual cycles, delayed conception, miscarriage, reduced lactating time, low birth weight, preterm birth, small for gestational age infants, and higher incidence of stillbirths and mortality among children (22)(23)(24)(25)(26)(27). PCB congeners may work in an aryl hydrocarbon receptor-dependent or -independent pathway (6,7,28).…”
mentioning
confidence: 99%
“…Although the cancer hazard posed by TCDD has received much attention over the past 20 years, its non-cancer hazard may be more important to the general public than the cancer hazard at current background doses (Greene et al, 2003). Exposure to high levels of dioxin has also been associated with adverse pregnancy outcomes (Tsukimori et al, 2008), including higher risk of birth defects and lower birth weight. Studies have shown that dioxins can not only affect hormone homeostasis (Gupta et al, 2006) and reproductive parameters (Mocarelli et al, 2008) in directly exposed individuals, but also have implications in hormone dysfunction (Baccarelli et al, 2008) and behavioral sexual dimorphism (Winneke et al, 2013) in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…According to the experiments on animals, some PCB congeners have carcinogenicity and this would be enhanced in cooperation with other chemicals. In 1968 and 1979, there were two serious PCBs pollution events: PCBs in a heat exchanger leaked into edible oil and resulted in 10,000 people poisoned (Tsukimori et al, 2008). Of the 209 PCBs congeners, the 12 dioxin-like and 6 indicator PCBs were usually of concern due to their high toxicity and high concentrations in the environment.…”
Section: Introductionmentioning
confidence: 99%